PELATIHAN DASAR-DASAR PENGGUNAAN MICROSOFT WORD UNTUK SISWA SD N 2 TULIKUP GIANYAR - Putu Safitri Pratiwi, Luh; Made Hendra Mahajaya Pramayasa, I; Putu Nanik Hendayanti, Ni; Made Pasek Pradnyana Wijaya, I (COVIT (Community Service of Tambusai), 2022)
Education has an important role in efforts to improve human resources in a better direction. Education is expected to be able to form students who can develop their attitudes, skills and intellectual intelligence so that they become skilled, intelligent and noble human beings. At this time of modernization the computer is no longer a foreign device. The use of computers has become an important part of the nation's students in schools. In terms of computer education, it can be used as a tool (media) in the teaching and learning process for both teachers and students. Students' knowledge of using computers, especially the Microsoft Word application at SD Negeri 2 Tulikup, is still relatively small, so that the assignments given at school do not yet use Microsoft Word. Therefore, computer training activities are needed, especially Microsoft Word training. On the bright side, children become more diligent and motivated to learn to concentrate. To achieve this goal, training and assistance have been carried out in the teaching and learning process of introducing information technology in the form of Microsoft Word. This training is conducted regularly and is accompanied by hands-on practice so that the students of SD Negeri 2 Tulikup find it easier to understand and remember. Based on the results of the monitoring and evaluation carried out, this community service activity went well and smoothly, seen from the enthusiasm of the students to learn and directly practice the material that had been taught. The participants were able to use existing tools in Microsoft Word. With this training, it is hoped that students will be more diligent in studying computers which will later be useful in completing school assignments and jobs related to technology. Keywords: Training, Microsoft Word; Elementary school